1988
DOI: 10.1104/pp.88.4.1291
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Sesquiterpene Cyclase and Suppression of Squalene Synthetase Activities in Plant Cell Cultures Treated with Fungal Elicitor

Abstract: Addition of elicitor, cell wall fragments of the fungus Phytophthora parasitica, to tobacco cell suspension cultures (Nicotiana tabacum) resulted in the rapid synthesis and secretion of large amounts of antibiotic sesquiterpenoids. Pulse-labeling experiments with I'4Ciacetate and PHI mevalonate demonstrated that the induction of sesquiterpenoid biosynthesis, maximal by 6 to 9 hours after elicitor addition to the cell cultures, was paralleled by a rapid and large decline in the incorporation rate of radioactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
160
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(169 citation statements)
references
References 20 publications
9
160
0
Order By: Relevance
“…In contrast, the rapid switches in terpenoid metabolism that occur upon pathogen infection have been extensively investigated. For example, when cell cultures of tobacco or potato are treated with fungal elicitors, there is an induction of sesquiterpenoid phytoalexin biosynthesis and a repression of sterol formation (Brindle et al, 1988;Vö geli and Chappell, 1988;Chappell, 1995). Enzymatic analyses have revealed that fungal elicitors activate farnesyl diphosphate-utilizing enzymes in phytoalexin biosynthesis while reducing the activity of squalene synthase, a branchpoint enzyme in sterol formation that also competes for farnesyl diphosphate.…”
Section: Enzyme Controlmentioning
confidence: 99%
“…In contrast, the rapid switches in terpenoid metabolism that occur upon pathogen infection have been extensively investigated. For example, when cell cultures of tobacco or potato are treated with fungal elicitors, there is an induction of sesquiterpenoid phytoalexin biosynthesis and a repression of sterol formation (Brindle et al, 1988;Vö geli and Chappell, 1988;Chappell, 1995). Enzymatic analyses have revealed that fungal elicitors activate farnesyl diphosphate-utilizing enzymes in phytoalexin biosynthesis while reducing the activity of squalene synthase, a branchpoint enzyme in sterol formation that also competes for farnesyl diphosphate.…”
Section: Enzyme Controlmentioning
confidence: 99%
“…In cell cultures of Nicotiana tabacum treated with a fungal elicitor, biotic elicitation can also cause coordinated inhibition of squalene synthase and induction of sesquiterpene cyclase resulting in a rapid decrease in phytosterol biosynthesis coincident with the induction and accumulation of novel terpenoids involved in the plant defense response (Threlfall and Whitehead, 1988;Voegeli and Chappell, 1988).…”
Section: Squalene Synthasesmentioning
confidence: 99%
“…Capsidiol biosynthesis is regulated by the expression of two key enzymes (see Scheme 1). 5-Epiaristolochene synthase catalyzes the cyclization of farnesyl diphosphate to the bicyclic intermediate 5-epiaristolochene (EA) 1,2 and is responsible for the diversion of farnesyl diphosphate from the mevalonate pathway toward antimicrobial compound biosynthesis (12,13). Recently, two highly homologous cDNAs for EA dihydroxylase (EAH) were isolated from Nicotiana tabacum and functionally expressed in yeast, and the encoded proteins were characterized as cytochrome P450 enzymes catalyzing the stereo-and regiospecific hydroxylation of EA at C-1 and C-3 (see Scheme 1) (14).…”
mentioning
confidence: 99%